Pengaruh Konflik Peran Ganda Dan Stress Kerja Terhadap Kinjerja Karyawan Fisip Universitas Lambung Mangkurat - Halimah; Setio Utomo (JURNAL BISNIS DAN PEMBANGUNAN, 2025)
Abstract: This research investigates the influence of bidirectional dual role conflict and work stress on female employee performance at the Faculty of Social and Political Sciences, Lambung Mangkurat University. The study addresses the critical gap in understanding how work-family and family-work conflicts impact performance through stress mediation mechanisms in Indonesian higher education contexts. Employing quantitative methodology with descriptive-explanatory design, data were collected from 56 female employees using structured questionnaires measured on five-point Likert scales. Partial Least Square-Structural Equation Modeling (PLS-SEM) was utilized to evaluate measurement and structural models simultaneously. Results demonstrate that work-family conflict does not exhibit direct significant influence on performance (P-value 0.161), yet significantly amplifies work stress (coefficient 0.492, P-value 0.000). Family-work conflict shows marginally significant negative impact on performance (P-value 0.050) and significantly increases stress levels (coefficient 0.323, P-value 0.008). Work stress demonstrates substantial negative influence on performance (coefficient -0.509, P-value 0.000), confirming its critical mediating role. Indirect effect analysis reveals that stress significantly mediates the relationship between dual role conflicts and performance, despite non-significant direct pathways. The study contributes theoretical insights into bidirectional conflict mechanisms and stress mediation pathways, providing empirical evidence for developing strategic human resource interventions focused on work-life balance policies and comprehensive stress management programs in academic institutions